A Bipolar Delayed Fluorescence Luminogen with Fast Reverse Intersystem Crossing and High Horizontal Dipole Orientation for High‐Performance Sky‐Blue and White OLEDs. Issue 5 (8th January 2022) - Fu, Yan; Liu, Hao; Yang, Dezhi; Ma, Dongge; Zhao, Zujin; Tang, Ben Zhong
Abstract: The development of robust luminescent materials plays a key role for organic light‐emitting diodes (OLEDs). Herein, a tailor‐made sky‐blue delayed fluorescence luminogen (DCPC‐BP‐SFAC) containing a carbonyl acceptor and spiro[acridine‐9, 9″‐fluorene] and 9, 9″‐(cyclohexane‐1, 1‐diylbis(4, 1‐phenylene))bis(9H‐carbazole) donors is explored, which holds merits of excellent thermal stability, strong photoluminescence, balanced carrier transport, and horizontal dipole orientation. Owing to a charge‐transfer dominated singlet state and a charge‐transfer and local‐excitation hybrid triplet state, DCPC‐BP‐SFAC has a small energy gap between singlet and triplet as well as a large spin–orbit coupling constant, which result in a fast reverse intersystem crossing process and thus efficient delayed fluorescence. High‐performance sky‐blue OLEDs with outstanding external quantum efficiencies (ηext ) reaching 32.6% are achieved based on DCPC‐BP‐SFAC, benefiting from high exciton utilization and large light out‐coupling efficiency. Moreover, using DCPC‐BP‐SFAC as blue emitter and host material simultaneously, efficient all‐fluorescence out‐of‐phase sensitizing white OLEDs without interlayer are fabricated, providing high ηext of up to 21.6% and stable warm‐white light with a high color rendering index of 84. The outstanding electroluminescence performances demonstrate the great potentials of DCPC‐BP‐SFAC in practical display and lighting devices. Abstract : A tailor‐made sky‐blue delayed fluorescence luminogen with strong photoluminescence, fast reverse intersystem crossing, balanced carrier transport, horizontal dipole orientation, and large light out‐coupling efficiency is explored, which furnishes outstanding external quantum efficiencies of 32.6% as emitter in sky‐blue organic light‐emitting diodes (OLEDs) and 21.6% as emitter and host simultaneously in all‐fluorescence white OLEDs.